Locating the Former Synagogue of Seduva, Lithuania - Schneider, Samuel G.; Beck, Joseph D.; Fuerstenberg, Madeline M.; Kofman, Chloe C.; Jol, Harry M. (My University, 2019)
Ground penetrating radar (GPR) was collected over a pavement parking lot in Šeduva, Lithuania, to search for a synagogue that was destroyed during the Soviet occupation of Lithuania. The GPR data was collected with a Sensors & Software pulseEKKO GPR equipped with 500 MHz antennae. The survey was collected over a grid that was 18m x 32m and a line spaced every 0.25m. The GPR line data was processed within the software packages: GFP_Edit and EKKO_Project 5. The results from the survey showed what are interpreted as structural walls and the outline of the previously standing synagogue.
Color poster with text, images, maps, and photographs.
Keywords: Ground penetrating radar (GPR); Šeduva, Lithuania; Posters